The Clinical Characteristics of New-Onset Epilepsy in the Elderly and Risk Factors for Treatment Outcomes of Antiseizure Medications - Qi, Jing; Liu, Xiao; Xu, Na; Wang, Qun (Frontiers in Neurology, 2022)
Objective: To describe the clinical characteristics of elderly patients with new-onset epilepsy in a Class A tertiary comprehensive hospital in north China and evaluate the treatment outcomes of antiseizure medications (ASMs). Investigating the factors affecting the treatment outcomes, to guide the drug treatment and judge the prognosis of elderly epilepsy patients. Methods: We included patients aged 60 years or older at the time of their first seizure between January 2014 and August 2020. Demographic characteristics, effects of ASM, and the proportion of 1-year and long-term seizure freedom were reported. Univariate analysis and binary logistic regression were used to identify factors potentially influencing treatment outcomes. Results: A total of 326 patients (median age 65 years, 67.2% male) were included. 185 (56.7%) patients who received the first ASM monotherapy achieved 1 year of seizure freedom in the early stage. Compared with structural etiology, unknown etiology was associated with higher likelihood of early seizure freedom (odds ratio [OR] = 0.545; p < 0.05). Conversely, comorbid intracranial malignant tumors, taking carbamazepine (CBZ), and sodium valproate (VPA) were associated with lower likelihood of seizure freedom (OR=3.527 vs 6.550 vs 8.829; p < 0.05). At long-term follow-up, 263 (80.6%) patients achieved seizure freedom, with 79.8% on monotherapy. Conclusions: Elderly patients with new-onset epilepsy responded well to initial ASMs treatment. Patients with intracranial malignant tumors and prescribed VPA and CBZ were less likely to achieve early seizure freedom, while those with unknown etiology had higher probabilities of achieving early seizure freedom than those with structural etiology.